2017
DOI: 10.1136/bmjopen-2017-016913
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the stem cell marker geneCD133are associated the clinical outcome in a cohort of Chinese non-small cell lung cancer patients

Abstract: ObjectivesTo evaluate the prognostic relevance of four functional single nucleotide polymorphisms (SNPs) in CD133 (rs2240688A>C, rs10022537T>A, rs7686732C>G, and rs3130C>T) on overall survival (OS) of non-small cell lung cancer (NSCLC) patients.DesignRetrospective cohort study.SettingDepartment of General Surgery, in a general hospital, Henan Province, China.ParticipantsNSCLC patients aged ≥18 years, who were not receiving preoperative neoadjuvant therapies and had a blood sample available for genotyping, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…This may be attributed to the fact that CD133 expression is closely related to cell proliferation, apoptosis, invasion and metastasis, and angiogenesis (39)(40)(41)(42). Furthermore, it has been shown that SNPs located in the 3'untranslated region (3'-UTR) region of the CD133 gene are associated with a variety of human tumors (38,43,44). SNPs in the 3'-UTR have also been shown to have functional effects on the control of mRNA stability and efficiency through the regulation of miRNA, including miR-34a, -101, -128, -137 and -1385 (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to the fact that CD133 expression is closely related to cell proliferation, apoptosis, invasion and metastasis, and angiogenesis (39)(40)(41)(42). Furthermore, it has been shown that SNPs located in the 3'untranslated region (3'-UTR) region of the CD133 gene are associated with a variety of human tumors (38,43,44). SNPs in the 3'-UTR have also been shown to have functional effects on the control of mRNA stability and efficiency through the regulation of miRNA, including miR-34a, -101, -128, -137 and -1385 (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%